KEPUASAN DAN LINGKUNGAN KERJA SERTA PENGARUHNYA TERHADAP TURNOVER INTENTION KARYAWAN PADA MELIA BALI HOTEL INDONESIA NUSA DUA - NI MADE ARYANI PUTRI; I KETUT PASEK; NI LUH MADE WIJAYATI; SAGUNG MAS SURYANIADI (GANEC SWARA, 2023)
The research -was titled "Satisfaction and Work Environment and Its Effect on Employee Turnover Intention at Melia Bali Indonesia Nusa" involving 85 employees as respondents. The purpose of this study was to determine the influence of job satisfaction (X1) and work environment (X2) on Turnover Intention (Y). The method used in this study was the analysis of multiple linear regression through the aid of the program SPSS 25. The data types in this study are quantitative descriptive. The analysis results of this study showed that the job satisfaction of a partial is negatively influential and significant to turnover intention with the significant value of 0,000 <0.05 with a tvalue -13.920 < ttable 1,66365. Work environments are partially influential negatively and significantly towards turnover intention with the significant value of0.000 <0.05 with a tvalue of - 3.933 > ttable 1,66365. Satisfaction and work environment simultaneously have a significant effect on turnover intention. With Fcount 132,974 > 3,11 and a significance value of 0.000 <0.05. With a coefficient of determination of 75,9%. This research is expected to assist companies in improving existing policies to reduce turnover intentions.